Manajemen kemitraan lembaga publik dan privat antara Pt Astra agro lestari dan pemerintah daerah Pasangkayu di desa martajaya - Novitasari Novitasari; lidya olivia balanda; Siti Nurfadila; Fikra Fikra; Phiter Boni Parubak; Dicky Candra Salatun; Nuraisyah Nuraisyah; Askar Mayusa; Muhammad Ahsan Samad (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Partnership Between Public and Private institutions are on important form of cooperation in supporting regional development and improving community welfare. This study aims ro examine the implementation of partnership management beetwen PT Astra Argo Lestari through PT Pasangkayu Regional Government in Martajaya Village. The focus of this research includes the forms of cooperatinon, the implementation process of the partnership, and the benefits experiencedby the Community troughCorporate Social Responsbility (CSR)Programs.The research method used was descriptive qualitative with data collection techniques consisting of observation, interviews, and documentation. The results showed that the partnership between PT Astra Agro Lestari and the Pasangkayu Regional Government was carried out through various CSR programs in the fields of health, environment, and community empowerment. The cooperation has provided positive impacts on improving health services, environmental cleanliness, and relationships among the company, local government, and the people of Martajaya Village. The public-private partnership demonstrates synergy between the company and the local government in supporting sustainable social development for the community.